Criteria for determining machinability and techniques of improving machinability of steel and alloys - Amin, A. K. M. Nurul (1993)
It has been established that during of steel and other work materials there is a definite cutting speed at which chip-tool-contact changes abruptly from contact with built-up-edge (BUE) formation to contact without BUE formation. This cutting speed has been termed as critical cutting speed, Vc. Intensity of wear of a tungsten carbide tool is minimum at a speed slightly lower that Vc, when a soft BUE protects the tool from intensive wear. In case of with Tungsten-Titanium carbide tool there is a second cutting speed, slightly above Vc at which a second peak of tool life is observed. These speeds have been referred to as optimum cutting speeds, Vopt1, and Vopt2 respectively. Since both these speeds have definite relationship with the critical cutting speed, Vc which has a specific value for every pair of work and tool materials and conditions of cutting, so the speed Vc may be used on an important criteria for determining machinability of work materials. Three different methods of determining cutting speed Vc has been discussed in this paper.